MicroRNA-124: A Key Player in Microglia-Mediated Inflammation in Neurological Diseases - Zhao, Jiuhan; He, Zhenwei; Wang, Jialu (Frontiers in Cellular Neuroscience, 2021)
Neurological disorders are mainly characterized by progressive neuron loss and neurological deterioration, which are important causes of human disability and death. The etiology of neurological disorders is complex and diverse; however, many types of neurological disorders usually have some similar pathological mechanisms, including neuroinflammatory response. In recent studies, various microRNAs (miRs), such as miR-21, miR-124, miR-146a, and miR-132, were shown to play a key role in the processes of neurological disorders by regulating neuroinflammatory response and may be feasible therapeutic targets. Microglia (MG) are the innate immune cells and play an important role in the physiological and pathological activities of the central nervous system (CNS). Recently, abnormal expression of miR-124 was shown associated with the occurrence and development of various neurological disorders via regulating MG function. In addition, miR-124 might be a promising biomarker and therapeutic target. The study of miR-124 in regulating MG function involved in pathogenesis of neurological disorders at different stages will provide new ideas for miR-124 as a therapeutic target for different neurological disorders.